Poly (ADP-Ribose) Polymerase 1 Regulates Cajal–Retzius Cell Development and Neural Precursor Cell Adhesion - Nelson, Megan M.; Hoff, J. Damon; Zeese, Mya L.; Corfas, Gabriel (Frontiers in Cell and Developmental Biology, 2021)
Poly (ADP-Ribose) Polymerase 1 (PARP1) is a ubiquitously expressed enzyme that regulates DNA damage repair, cell death, inflammation, and transcription. PARP1 functions by adding ADP-ribose polymers (PAR) to proteins including itself, using NAD+ as a donor. This post-translational modification known as PARylation results in changes in the activity of PARP1 and its substrate proteins and has been linked to the pathogenesis of various neurological diseases. PARP1 KO mice display schizophrenia-like behaviors, have impaired memory formation, and have defects in neuronal proliferation and survival, while mutations in genes that affect PARylation have been associated with intellectual disability, psychosis, neurodegeneration, and stroke in humans. Yet, the roles of PARP1 in brain development have not been extensively studied. We now find that loss of PARP1 leads to defects in brain development and increased neuronal density at birth. We further demonstrate that PARP1 loss increases the expression levels of genes associated with neuronal migration and adhesion in the E15.5 cerebral cortex, including Reln. This correlates with an increased number of Cajal-Retzius (CR) cells in vivo and in cultures of embryonic neural progenitor cells (NPCs) derived from the PARP1 KO cortex. Furthermore, PARP1 loss leads to increased NPC adhesion to N-cadherin, like that induced by experimental exposure to Reelin. Taken together, these results uncover a novel role for PARP1 in brain development, i.e., regulation of CR cells, neuronal density, and cell adhesion.